The Impact of Some Biochemical Factors in Increasing Disease Pathogenicity of Systemic Lupus Erythematosus - Kuba, Rasha H.; Ahmed, Esraa A. (Iraqi Journal of Science, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease with unknown etiology, though genetic and environmental factors appear to play a role in its pathogenesis. In particular, infectious processes are linked to the onset and exacerbation of SLE. The aim of the current study was to understand the relationship between some biochemical factors in SLE patients. 105 blood samples from both genders were collected.  ELISA technique was used for detecting specific procalcitonin, vitamin D and calcium. The results of this study showed that SLE patients recorded the lowest percentages of calcium (7.36 ± 0.10 mg/dl) than control (11.97 ± 2.12 mg/dl), and vitamin D (7.79 ± 0.58 pg/ml) than control (22.10 ± 4.83 pg/mL). And the highest percentage of procalcitonin level in serum (35.73 ± 4.08 pg/ml) compared to the control (11.57 ± 5.35 pg/ml). Furthermore, the seroprevalence of SLE patients was the highest in the 31-45 years age group, and the majority of them were females which accounted 87.5 %. In this study vitamin D and calcium were the lowest in SLE patients. The severity of disease symptoms in SLE patients may be caused by specific alterations in vitamin D and calcium homeostasis. And procalcitonin was the highest in SLE patents.